2022
DOI: 10.1002/crat.202200014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnesium Hydroxide Using Post‐Reaction Filtrate as Ammonia Carrier and Morphology Analysis

Abstract: This study proposes an advanced technology using post‐reaction filtrate as an ammonia carrier to synthesize magnesium hydroxide (MH) with small particles, which can benefit subsequent hydrothermal modification. In this work, the limitation of ammonia gas and ammonia water methods is avoided. The impact of operating parameters including MgCl2 concentration, temperature, ammonia‐to‐magnesium molar ratio, feed rate, volume of ammonia mother liquor and aging time on the magnesium yield, particle size, and morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the ordinary synthesis process, lamellar crystals generally do not aggregate and grow in the [0 0 1] direction, but the crystals would aggregate in the (1 0 0), (1 1 0), (1 0 2), and (1 0 1) directions to reduce the overall energy, finally growing into flower-shape crystals. [32] In addition, this also explains the reason for MH crystals after hydrothermal treatment exhibit lamellar morphology with good dispersion.…”
Section: Structure and Surface Energy Of Crystal Planesmentioning
confidence: 93%
See 2 more Smart Citations
“…In the ordinary synthesis process, lamellar crystals generally do not aggregate and grow in the [0 0 1] direction, but the crystals would aggregate in the (1 0 0), (1 1 0), (1 0 2), and (1 0 1) directions to reduce the overall energy, finally growing into flower-shape crystals. [32] In addition, this also explains the reason for MH crystals after hydrothermal treatment exhibit lamellar morphology with good dispersion.…”
Section: Structure and Surface Energy Of Crystal Planesmentioning
confidence: 93%
“…The precursors MH with different morphologies were prepared under different experimental conditions in the previous work. [32] The small round flaky precursors were synthesized with 4 mol L −1 MgCl 2 solution and 8 mol L −1 NaOH solution at 298 K with the stirring rate of 300 rpm. Specifically, 50 mL NaOH solution was added into a jacketed reactor containing 50 mL MgCl 2 solution at the feed rate of 25 mL min −1 , then the suspension was filtered immediately after the reaction.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous work, the idea crystal habit of MH could be predicted by Bravais–Friedel Donnay–Harker and Growth Morphology methods in the morphology module, which showed that the morphology of the MH crystal was regular hexagonal plate. As shown in Figure , the (0 0 1) plane determines the diameter of the plate, and the (1 1 0) plane mainly determines the thickness of the plate.…”
Section: Methodsmentioning
confidence: 99%
“…The MH precursor was prepared under optimal synthesis conditions in the previous work. 23 2.1.2. Experimental Procedures.…”
Section: Experimental Methods 211 Materials Naoh Andmentioning
confidence: 99%